Atrial fibrillation management strategies and early mortality after myocardial infarction: results from the Valsartan in Acute Myocardial Infarction (VALIANT) Trial. Issue 11 (20th April 2010) - Nilsson, Kent R; Al-Khatib, Sana M; Zhou, Yi; Pieper, Karen; White, Harvey D; Maggioni, Aldo P; Kober, Lars; Granger, Christopher B; Lewis, Eldrin F; McMurray, John J V; Califf, Robert M; Velazquez, Eric J
Abstract : Objective: The management of patients with atrial fibrillation (AF) following a myocardial infarction (MI) remains uncertain. This study compared a rate control strategy to an anti-arrhythmic-based rhythm control strategy for the treatment of AF following myocardial infarction. Design, setting and patients: We studied 1131 patients with AF after MI who were enrolled in the Valsartan in Acute Myocardial Infarction Trial (VALIANT). We classified patients into those treated with a rhythm control strategy (n=371) and those treated with a rate control strategy (n=760). Main outcomes measures: Using Cox models, we compared the two groups with respect to both death and stroke during two different time periods after randomisation for which data collection had been pre-specified: 0–45 days and 45–1096 days. Results: After adjustment, a rhythm control strategy was found to be associated with increased early mortality (0–45 days: HR: 1.9, 95% CI 1.2 to 3.0, p=0.004) but not late mortality (45–1096 days: HR 1.1, 95% CI 0.9 to 1.4, p=0.45). No difference was observed in the incidence of stroke (0–45 days: HR 1.2, 95% CI 0.4 to 3.7, p=0.73; 45–1096 days: HR 0.6, 95% CI 0.3 to 1.3, p=0.21). Conclusions: In patients with AF after an MI, an anti-arrhythmic drug-based rhythm control strategy is associated with excess 45-day mortality compared with a rate control strategy, but is not associated with increased mortality outside of the immediate peri-infarct period. These results potentially identify a patient population in whom the use of anti-arrhythmic drug therapy may portend an increased risk of death.